Kemampuan Guru dalam Penggunaan Media Pembelajaran di MAN 1 Bireuen - Zikri Fonna; Mujiburrahman Mujiburrahman; Tihalimah Tihalimah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The development of science and technology increasingly encourages renewal efforts in the use of technological results in the learning process. So that teachers are able to use the tools that have been provided by the school in the form of modern or traditional technology, and choose what media to use, and it is possible that these tools are in accordance with the developments and demands of the times. In MAN 1 Bireuen, innovative learning media based on information and communication technology are very helpful for teachers in the learning process, but there are still teachers who have not been able to use them, teachers also have difficulty using IT media and teachers also have difficulty in determining learning media that are in accordance with the material. The purpose of this study was to determine the teacher's ability to use learning media at MAN 1 Bireuen, and to determine the teacher's constraints in using learning media at MAN 1 Bireuen. The research used is qualitative using a descriptive approach. The research subjects were the principal and two teachers. Data collection techniques used observation, interviews and documentation. The results of this study indicate that the ability of teachers to use learning media at MAN 1 Bireuen is still not good, because there are teachers who cannot enter the power point system into the media. To use learning media, not all can master learning media, except for young teachers who are easy to use media and teachers who have not been able to use media for a long time. Constraints of the head of MAN 1 Bireuen in the use of learning media. First, very limited learning media, such as in completing learning media tools. Second, the lack of funds is also an obstacle for MAN 1 Bireuen. Third, the ability of teachers who are still lacking in the use of media. Fourth, the power grid sometimes goes out.